Relief to Spanish seamen: amounts paid by the Union (accounts)
025a-0092-001 NATIONAL UNION OF SEAMEN. RELIEF TO SPANISH SEAMEN. AMOUNTS PAID BY THE UNION. DATE. TO WHOM PAID. AMOUNT. 1.5.39 M. Galdeano £2 2 0 8.5.39 ditto £2 2 0 15.5.39 ditto £2 2 0 1.5.39 Mrs.C.Price £1 14 0 8.5.39 ditto £1 14 0 15.5.39 ditto £1 14 0 4.5.39 Liverpool Sailors' Home £21 17 6 11.5.39 ditto £27 5 0 10.5.39 ditto £20 0 0 3.5.39 Hull Sailors' Home £17 0 0 10.5.39 ditto £17 0 0 ' 3.5.39 W. Coomber, Hull £11 1 0 10.5.39 ditto £11 1 0 1.5.39 Peoples Hostels Ltd., Newcastle £33 5 0 9.5.39 ditto £21 5 0 16.5.39 ditto £21 5 0 9.5.39 W.G.Emms, Sundry expenses 12 6 3.5.39 W. Jones, Cardiff £13 16 6 9.5.39 ditto £1 10 0 11.5.39 ditto £15 6 6 4.5.39 Plymouth &, District Refugee Spanish Childrens Fund. £8 0 0 17.5.39 ditto £16 0 0 13.5.39 West Hartlepool Corporation £27 4 0 13.5.39 Newton Watson £1 14 0 13.5.39 A.J. & E.G.Harwood £3 8 0 1.5.39 Missions to Seamen, Sunderland £1 15 0 15.5.39 ditto £1 15 0 8.5.39 ditto £1 15 0 1.5.39 G. D&Americo, Sunderland £2 9 6 8.5.39 ditto £2 3 6 15.5.39 ditto £2 3 6 1.5.39 Salvation Army Homes, Sunderland £17 2 6 8.5.39 ditto £11 7 6 15.5.39 ditto £11 10 10.5.39 Royal National Mission to Deep Sea Fishermen,Grimsby £18 16 0 16.5.39 ditto £18 16 0 £ 389 12 6 13.5.39. REFUND OVERPAID W. JONES 1 10 0 £388 2 6 PLUS ADMINISTRATION EXPENSES £1 17 6 GRAND TOTAL £390. 0. 0. 292/946/25a/92